Prediction of anterior open-bite development after stabilization splint treatment in patients with temporomandibular disorder. Issue 4 (4th July 2022) - Oh, Jae-Won; Ahn, Yong-Woo; Jeong, Sung-Hee; Ju, Hye-Min; Song, Byong-Sop; Ok, Soo-Min
ABSTRACT: Objective: To assess the dentoskeletal factors of patients with temporomandibular disorders (TMDs) that can predict anterior open-bite development after stabilization splint treatment (ST). Methods: Eighty-seven TMD patients were classified into three groups according to the degree of overbite changes after ST. Statistically significant differences in dental and skeletal measurements before ST among the groups were investigated. Results: Pre-ST dental and skeletal measurements that were significantly different among the groups were upper central incisor (U1) to point A-pogonion (A-Pog), facial height ratio (FHR), A point–nasion-B point angle (ANB), Wits appraisal, ramus height, angle of convexity, and sella to condylion. Among these factors, FHR, ramus height, and sella to condylion had a positive relationship with overbite changes. Discussion: Dentoskeletal factors, i.e., FHR, ramus height, and sella to condylion, can predict anterior open-bite development after ST in TMD patients.